Designing a model to determine the preferred Islamic contract for a bank facilities applicant - Jahani, Marzieh; Mohammadi, Parastoo (International Journal of Engineering and Technology, 2018)
This paper aims to present a model to determine the preferred Islamic contract for the bank facilities applicant in the industrial sector. For this purpose we use a consolidated method which includes the compromise solution multi-criteria optimization in the first phase, and the calculation of the cost of financing for the applicant of facilities in the second phase. Afterwards, by using the output of the both-phase, the preferred Islamic contract based on the combinational criterion has been determined for the applicant of the facilities. According to the fact that in the financing of the projects, in addition to the criteria related to the cost of financing, the qualitative criteria are also important, so both the qualitative and quantitative criteria have been considered in this research. In this study, we used four widely applied Islamic contracts (Jo’aalah Instalment sales, Hire purchase, Participation). The assessment criteria of the Islamic contracts have been extracted in the form of a questionnaire based on the previous studies and the expert’s point of view. In the first phase, the Analytic Hierarchy Process (AHP) has been used in order to determine the weights of the evaluation criteria of the Islamic contracts; and, in order to select an appropriate contract for the applicant, the compromise solution multi-criteria optimization approach (VIKOR), which is based on the decision matrix, was used. In the second phase, the cost of financing from the bank was estimated for the applicant of the facilities in the four contracts. Finally, the obtained results of the qualitative questionnaire and the cost of financing from the bank have been combined; thus, the preferred contract for the applicant of facilities has been determined based on a combinational criterion.